The Process of Constructing an Inter-Korean Identity Reflective of the Two Koreas: North Korean Refugee Students’ Hybrid Identity in South Korea. - Kim H (http://www.sciencepg.com/journal/ijecs, 2024)
As of March 2024, 34,121 North Korean refugees reside in South Korea, with 12% enrolled in schools. Despite being automatically granted South Korean citizenship upon arrival, these refugees face social exclusion and marginalization, effectively forming a second class within South Korean society. The 70-year division between the two Koreans has resulted in vastly different lifestyle, making it challenging for North Korean refugees to adapt. This difficulty is compounded by a prejudiced social reception and discrimination toward their North Korean identity. The study aims to explore the daily experiences of North Korean refugees with their newfound South Korean citizenship, employing Straussian grounded theory and semi-structured interviews. The study recruited 17 North Korean refugees, including five with experience in elementary, middle and high schools, and five parents with school-going children. The findings reveal that academic deficits, exacerbated by discrimination and stereotypes linked to their North Korean identity, result in a disparity between their legal citizenship and school participation. In response, North Korean refugee students adopt a strategy of "being one of them,‟ leveraging ethnic homogeneity to facilitate interactions with their South Korean peers. These interactions enable the formation of supportive networks and foster the development of an inter-Korean identity reflective of both Koreas. The study underscores the critical role of multicultural education in achieving educational equality for North Korean refugee students and advocates for social bridging programs that acknowledge and embrace the differences of refugees. Despite being granted citizenship, they continue to be treated as outsiders within South Korean society.
Keywords: Citizenship; Multicultural Education; North Korean Refugee Students; Social Bridging programs; South Korea